Do we really understand quantum mechanics? - Laloe, Franck (Cambridge University Press, 2019)
"Quantum mechanics is a fantastically successful theory that has impacted on many areas of physics, from pure theory to applications. However, it is difficult to interpret, and philosophical contradictions and counter-intuitive results are apparent at a fundamental level. In this book, Laloë presents our current understanding of the theory"--